INFLUENCE OF FOLIAR SPRAY WITH AMINO ACIDS AND SEAWEED EXTRACT COMBINED WITH MICROELEMENTS AND CALCIUM ON GROWTH, FLOWERING AND YIELD OF HYMENOCALLIS SPECIOSA L. - M. Barsoom; Nermeen Abdul-Moneem; Evon Khella (Scientific Journal of Flowers and Ornamental Plants)
The present study aimed to investigate the beneficial effects of foliar spraying with amino acids and seaweed extract each at concentrations of 1.0, 1.5, and 2.0 ml/l alone or with the addition of a mixture of microelements at 0.5 g/l and calcium at 0.25 ml/l on vegetative growth, flowering, bulb production, and chemical components of Hymenocallis speciosa L. The current study was conducted at the Ornamental Plants and Landscape Gardening Res. Dept. Nursery, Hort. Res. Inst., ARC, Giza, Egypt, during the 2022 and 2023 seasons. Plants were treated with amino acids as a biostimulant at concentrations of 2 ml/l, which gave an increase in most growth characteristics as well as the same effect when using seaweed extract compared with the control. Also, when plants were treated with amino acids at 2.0 ml/l with a mixture of microelements at 0.5 g/l, it led to a significant increase in the values of morphological parameters included plant height, fresh weight of vegetative growth, number of leaves/plant, leaf area,  root length, fresh weight of roots, spike length, flower diameter, flower weight, fresh weight of bulb and bulb circumference. It also led to an increase in the content of chlorophylls and carotenoids in leaves and total carbohydrates and N, P and K in new bulbs. Likewise, spraying the plant with seaweed extract at a rate of 2.0 ml/l with the addition of a mixture of microelements at a rate of 0.5 g/l led to an increase in most plant characteristics. However, the treatment with amino acids was superior in some of the studied plant characteristics compared to treatment with seaweed extract.